1975
DOI: 10.1530/acta.0.0790789
|View full text |Cite
|
Sign up to set email alerts
|

The Pharmacology and Metabolism of Testosterone Undecanoate (Tu), a New Orally Active Androgen

Abstract: Testosterone undecanoate (TU), either dissolved in arachis oil or as micro-crystal suspension, displays androgenic activity on oral administration to rats in the Hershberger test. The solution in arachis oil is more active than the crystal suspension. When [3H]TU is administered orally to rats, most of it is metabolized in the intestinal wall. The majority of the metabolites probably lose their undecanoate group and are absorbed via the portal vein. The non-metabolized [3H]TU and at least two metabolites are a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
46
1
4

Year Published

1979
1979
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 95 publications
(55 citation statements)
references
References 1 publication
4
46
1
4
Order By: Relevance
“…After perfusion of an MU emulsion through an isolated section of jejunum in anesthetized rats, the concentrations of MU in blood draining the perfused intestinal segment were below the limits of quantification at all the time points, whereas appearance of M was clearly evident (data not shown). This finding confirmed that a significant proportion of the presystemic conversion of MU to M occurred in the enterocyte, consistent with previous reports for TU (Coert et al, 1975;Horst et al, 1976). Unpublished investigations have also shown that plasma esterases play a negligible role in the hydrolysis of MU and that hydrolysis by hepatic esterases is considerably more avid (data on file, Schering Plough).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…After perfusion of an MU emulsion through an isolated section of jejunum in anesthetized rats, the concentrations of MU in blood draining the perfused intestinal segment were below the limits of quantification at all the time points, whereas appearance of M was clearly evident (data not shown). This finding confirmed that a significant proportion of the presystemic conversion of MU to M occurred in the enterocyte, consistent with previous reports for TU (Coert et al, 1975;Horst et al, 1976). Unpublished investigations have also shown that plasma esterases play a negligible role in the hydrolysis of MU and that hydrolysis by hepatic esterases is considerably more avid (data on file, Schering Plough).…”
Section: Discussionsupporting
confidence: 91%
“…The use of prodrugs is one approach that has been used successfully to increase the oral bioavailability of highly metabolized compounds (Stella et al, 2007). In the case of testosterone, previous studies have shown that oral administration of testosterone esters may be used to facilitate effective testosterone exposure (Coert et al, 1975;Noguchi et al, 1985), and an oral formulation for the administration of testosterone undecanoate (TU) (Andriol Testocaps; Schering Plough, Kenilworth, NJ) is currently marketed in several countries. The bioavailability of testosterone after oral administration of TU is low and predominantly attributable to lymphatic transport of the lipophilic ester prodrug followed by postabsorptive cleavage to release the active testosterone .…”
mentioning
confidence: 99%
“…This process can be advantageous from a PK perspective, since absorption into the lymph system rather than portal blood bypasses the liver and avoids first-pass metabolism (22). This benefit is exploited for several drugs, such as orally administered testosterone (testosterone undecanoate prodrug) (47)(48)(49), that are ineffective due to their extensive first-pass metabolism. Alternatively, from a drug targeting perspective, preferential absorption into the lymphatic system can be used to target drugs to treat lymphatic cancers (50,51) and is also important for antiviral medication for protection of B and T lymphocytes (52)(53)(54).…”
Section: Lymphatic Targetingmentioning
confidence: 99%
“…The simplest form of the three, lipophilic esters/ethers, also has the most limited success. The results often show that the extensive pre-absorptive hydrolysis circumvents lymphatic transport; however, some success has been noted for delivery of highly potent hormone drugs such as testosterone (48,49,55). In strategies utilizing glycerides to enhance lymphatic transport, the site of drug attachment to the glyceride is an important consideration.…”
Section: Lymphatic Targetingmentioning
confidence: 99%
“…Apregoa-se que o seu efeito hepático possa ser menor que o da metiltestosterona, visto que, após a absorção intestinal, sofre um desvio do sistema porta e se dirige ao ducto toráxico. Esse caminho para chegar ao sangue através da veia subclávia se dá pelo fato de possuir uma cadeia alifática e ser transportada na linfa junto com os lipídios (Coert et al, 1975).…”
Section: Como Empregar Os Androgêniosunclassified